Population genetic structure of a major reef-building coral species Acropora downingi in northeastern Arabian Peninsula - Felipe Torquato (14158845) (2022)
Current seawater temperatures around the northeastern Arabian Peninsula resemble future global forecasts as temperatures > 35 °C are commonly observed in summer. To provide a more fundamental aim of understanding the structure of wild populations in extreme environmental conditions, we conducted a population genetic study of a widespread, regional endemic table coral species, Acropora downingi, across the northeastern Arabian Peninsula. A total of 63 samples were collected in the southern Arabian/Persian Gulf (Abu Dhabi and Qatar) and the Sea of Oman (northeastern Oman). Using RAD-seq techniques, we described the population structure of A. downingi across the study area. Pairwise G’st and distance-based analyses using neutral markers displayed two distinct genetic clusters: one represented by Arabian/Persian Gulf individuals, and the other by Sea of Oman individuals. Nevertheless, a model-based method applied to the genetic data suggested a panmictic population encompassing both seas. Hypotheses to explain the distinctiveness of phylogeographic subregions in the northeastern Arabian Peninsula rely on either (1) bottleneck events due to successive mass coral bleaching, (2) recent founder effect, (3) ecological speciation due to the large spatial gradients in physical conditions, or (4) the combination of seascape features, ocean circulation and larval traits. Neutral markers indicated a slightly structured population of A. downingi, which exclude the ecological speciation hypothesis. Future studies across a broader range of organisms are required to furnish evidence for existing hypotheses explaining a population structure observed in the study area. Though this is the most thermally tolerant acroporid species worldwide, A. downingi corals in the Arabian/Persian Gulf have undergone major mortality events over the past three decades. Therefore, the present genetic study has important implications for understanding patterns and processes of differentiation in this group, whose populations may be pushed to extinction as the Arabian/Persian Gulf warms. Other Information Published in: Coral Reefs License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00338-021-02158-y